Oil bioremediation in soils contaminated with oil spills in tropical environments - MARTÍNEZ-RIVERA,ALEJANDRO (2021)
Abstract Bioremediation techniques like bioaugmentation and/or biostimulation are an economical and environmentally friendly procedure which emerged as the most advantageous methodology for treatment of contaminated sites by oil spills pollutants. This research uses a tropical soil contaminated with oil based drilling fluids (OBMs) and drill cuttings were evaluating at laboratory scale. Seven treatments were implemented separately: (C) control; (A) natural attenuation; (B) compost (Bs) nutrients; (BsT) nutrients and tween 80; (BsTL) nutrients, tween 80, leonardite, and (BL) nutrients, tween 80, leonardite and d-limonene. For three months, changes in Total Petroleum Hydrocarbons (TPH) soil microbial counts and activity were monitored as indicators of biodegradation. In order to evaluate the efficiency of treatments in the microcosm experiments. After 90 days of incubation hydrocarbon biodegradation is 76.2% (C), 28.6% (A), 76.2% (B), 66.7% (Bs), 83.3% (BsT), 69% (BsTL) and 88.1% (BL), respectively. Scanning electron microscopy (SEM) of OBMs evidenced absence of heavy metals. Biodiversity analysis showed a decrease in bacterial diversity and a rise in tolerant genus of hydrocarbons such as Nocardiodes, Streptomyces, Dietzia and Advenella. The co-substrate and stimulants had synergistic effect on the biological degradation of hydrocarbons. This research suggests that the implementation of bioaugmentation and biostimulation methods will be used a larger scale in contaminated sites.